The effect of bilateral oophorectomy on bone mineral density - (:unkn) unknown (SPRINGER, 2006)
The objective of this study is to investigate the effect of bilateral oophorectomy with total abdominal hysterectomy on bone loss, comparing the cases having surgery before and after the menopause. Bone mineral density (BMD) measurements were obtained from the lumbar spine and femoral neck of totally 127 cases. Out of 127, 105 had surgery before menopause and 22 cases were operated on postmenopausally. The results were compared with the USA normal values. The average age of surgical menopause (SM) cases was 48.45 years with a mean duration of menopause of 5.77 years. The average height and weight were 157.67 cm and 68.19 kg, respectively. The average age of cases having surgery after menopause (SAM) was 62.45 years with a mean duration of 5.59 years after the surgery (duration after menopause is 13.23 years). The average height and weight were 157.45 cm and 73.55 kg, respectively. The average of BMD measurements of lumbar spines L2-L4 was 1.04 gr/cm(2) (BMD = 85.65% and T score = -0.96) in the cases with SM. On the contrary, the average of the BMD measurements of lumbar spines L2-L4 was 1.05 gr/cm(2) (BMD = 101.14% and T score = 0.24) in the cases with SAM. The average of the BMD measurements of femoral neck was 0.85 gr/cm(2) (BMD = 91.39% and T score = -0.64) in the cases with SM. On the contrary, the average of the BMD measurements of femoral neck was 0.82 gr/cm(2) (BMD = 96.69% and T score = -0.31) in the cases with SAM. The bilateral oophorectomy as a surgical procedure is not a statistically significant factor for the acceleration of the bone loss. The main points are the age and the duration of menopause of the patient affecting the bone loss if the surgery is performed before menopause.
Keywords: bone mineral density; bilateral oophorectomy; surgical menopause; QUANTITATIVE COMPUTED-TOMOGRAPHY; DUAL-PHOTON-ABSORPTIOMETRY; MENOPAUSE-RELATED CHANGES; X-RAY ABSORPTIOMETRY; POSTMENOPAUSAL WOMEN; RELATIVE CONTRIBUTIONS; PROXIMAL FEMUR; GENETIC-DETERMINANTS; AXIAL SKELETON; LUMBAR SPINE